Rodzice a nowomedialne wspomaganie współczesnej polskiej szkoły (raport z badań) - MICHNIUK, ANNA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Anna Michniuk, Rodzice a nowomedialne wspomaganie współczesnej polskiej szkoły (raport z badań) [Parents and new media in modern Polish schools]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 23, Poznań 2018. Pp. 249-266. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.23.15 The article presents some of the conclusions of the research carried out in 2016 among the junior high schools located in lubuskie voiewodship. One of the subjects of the research was the parents of new media support for modern school assess. The text presents parents’ opinions on the new media activity of students, support of new media in the teaching – learning process, building contact between the school and parents and also (auto)promotion of the school. The article also contains a short description of the new media activity of parents of contemporary teenagers and characteristic of the media world in which modern parents were brought up.